Pathogenesis and Treatment of Non-Alcoholic Steatohepatitis and Its Fibrosis: A Systematic Review - Talha Ahmed, Sana Farooq, Muhammad Ashir Naveed, Ali Shahzad, Waleed Rehman, Tauqeer Haider (Students’ Supplement of Journal of Rawalpindi Medical College, 2025)
Introduction: Non-Alcoholic Steatohepatitis is a slow-developing liver disease characterized by fat in the liver, inflammation, and scarring. Although there are many treatments, no standard pharmacotherapy is approved globally. Objectives: This systematic review aims to enhance critical care practice by synthesizing evidence from recent trials on the pathogenesis and treatment of Non-Alcoholic Steatohepatitis and its fibrosis. Methodology: This systematic review was conducted according to the PRISMA principles. The literature was searched using text terms and controlled vocabulary, employing Boolean operators "AND," "OR," and various combinations across PubMed, Embase, and the Cochrane Library. Open-access, full-text English papers from 2014 to 2024, involving humans, were selected. The quality was assessed using ROB 2.0, and the evidence was appraised using GRADE. Fourteen RCTs were analyzed for methodological quality. The GRADE tool categorized two high ROB RCTs as "low quality." However, two RCTs had low ROB and were classified as "High quality." Ten RCTs had uncertain ROB, lowering the evidence by one point to "Moderate quality." Results: This review discusses clinical trials involving GLP-1 receptor agonists, THR-β agonists, pan-PPAR agonists, FGF21 analogues, and bariatric surgery. While GLP-1 agonists and resmetirom improve liver fat reduction, lanifibranor can also decrease fibrosis. Bariatric surgery is the best option for NASH in 56-70% of cases, but there are issues like incomplete fibrosis reversal and lack of long-term evidence. Conclusion: Non-alcoholic steatohepatitis (NASH) remains a challenging condition influenced by multiple factors, and there is currently no universally accepted treatment. Promising results have been seen with certain metabolic drugs and agents targeting multiple pathways, and bariatric surgery continues to show strong results for those who qualify. Future research should focus on combination therapies, exploring new antifibrotic therapies, and genetically based treatments.